Computational paleontology - Elewa, Ashraf M. (Springer, 2011)
Computational paleontology is simply a term applied to the use of computers and their facilities in the field of paleontology. However, we should be precise in describing the term when explaining the main themes of this motivating and attractive scientific field. The uppermost aim of this book is to explain how computation can be used to bring fossils to life and the past to present. For paleontologists computers save time and costs, interpret mysterious events precisely and accurately as welll as visualizing ancient life definitely and undeniabl